EXPLORING STUDENTS` VOCABULARY LEVEL - Nur Asdila; Mawardin M. Said; Afrillia Anggreni (Tadulako University, 2022)
The objective of this research is to identify the vocabulary level of grade VIII students at SMP Al-Azhar Mandiri Palu. This research is descriptive qualitative method which the results are tabulated and described. Data collection techniques are test and interview. The steps to analyze the data are to calculate the average score of each level and then the percentage of the average score. The results show that the percentage of average score on 2000 word level is 83.6%, 3000 word level is 81%, 5000 word level is 63%, 10000 word level is 21.6% and AWL (Academic Word List) is 77%. In conclusion, the grade VIII students at SMP Al-Azhar Mandiri Palu mastery vocabulary in high frequency word at 2000 and 3000 words level. The vocabulary most students have is nouns.